Implications on the use of videos in mathematics teaching in distance courses - Costa, Rosicacia Florencio; Lago Souto, Daise Pereira [UNESP] (Univ Federal Sergipe, 2017)
This article presents results of an empirical research whose objective is to highlight some implications on the use of videos in Mathematics. Specifically, in this research, this curricular component is characterized as a service discipline, which was taught in Distance Education courses (EAD)-(UAB) Open University System. To this end, we rely on the theoretical-methodological perspective called Seres-Humans-With-Media System. The research methodology is qualitative, since there is no concern with numerical representativeness, having as main procedures for data production, interview, questionnaire and participant observation. The subjects were the academics of the courses of Bachelor of Administration, Licentiate in Physics, Degree in Chemistry and the Technologist in System for Internet course of the institutions of Education of the State of Mato Grosso. The results indicated that the main implications in the use of videos are directly related to the learning of the students, in a collective and collaborative work.
Keywords: Teaching; Distance Education; Mathematics; Digital Technologies